Effects of the Modification of Negative Self-Statements on Reducing Academic Procrastination and Improving Academic Self-Efficacy - Abu-Zreik, Mohammed; Jaradat, Abdul-Kareem (Jordan Journal of Educational Sciences, 2013)
This study aimed to investigate the effects of the modification of procrastination producing self-statements on reducing academic procrastination and improving academic self-efficacy among a sample of tenth grade students. To achieve these objectives, two scales were developed one for academic procrastination, and the other for academic self-efficacy. The population of the study consisted of 120 tenth grade students at one of Al-Ramtha district schools, Jordan. Based on the scores of these students on the procrastination scale, 33 students were identified as procrastinators, who were randomly assigned to two groups, an experimental group and a control group. The experimental group received a program based on the modification of procrastination producing self-statements, while the control group didn’t receive any treatment. Results indicated that the treatment program was significantly (p<0.05) more effective in reducing procrastination and improving self-efficacy than no treatment at post and follow up assessment.